T3/ZOOM w edukacji akademickiej (poszukiwanie tematów prac dyplomowych przez studentów) - Olczak, Małgorzata (Wydawnictwo Naukowe UAM, 2016)
Problem finding is described as behaviours, attitudes and cognitive processes that are responsible for creating a vision, posing and formulating problems. Problem finding is an alternative towards behaviours, attitudes and processes participating in solving problems (Jay, Perkins 1997). Problem finding constitutes a significant part of problem7based thinking related to the processes of discovering, formulating and reformulating problems (Szmidt 2003). It is active in “the first phase of solving problems when becoming curious about a situation we try to realise the difficulty and formulate a question that would adequately reflect the situation we find ourselves in as well as the goal we strive for” (Szmidt 2003, 23 [own transl.]). Hence, the question becomes the main element of the process of searching for the problem because it satisfies the cognitive anxiety, while the answer is the central element of the process of solving problems (Arlin 1990). The author analyzed problem finding in the area of polytechnic education. She proposed employing her original T3/ZOOM technique of finding problems and cognitive tasks for the search for Bachelor’s thesis topics by the students.
T3/ZOOM in Academic Education (Students’ Search for The Diploma Theses’ Topics)
Keywords: pedagogy of creativity; problem finding; diploma thesis